2015
DOI: 10.1186/s12933-015-0245-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum osteocalcin level and carotid intima-media thickness in a metabolically healthy Chinese population

Abstract: BackgroundThe relationship between osteocalcin and atherosclerosis remains unclear. This might be due to different degrees of confounding from factors that are associated with serum osteocalcin level, such as metabolic-related variables. This study aimed to investigate the relationship between serum osteocalcin level and carotid intima-media thickness (C-IMT) in a metabolically healthy population.MethodsA total of 476 subjects with normal values for weight, glucose tolerance, blood pressure, and lipids (age ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
6
18
0
Order By: Relevance
“…Then, it begins to decrease at the age of 20 years in males and females [16]. It has been reported that the serum OC level is 50-150 ng/mL in children, whereas it is 12-20 ng/mL in healthy adults [17]. In our study, the OC level was 87.7±32.7…”
Section: Mortality Rate Of Fop Patientssupporting
confidence: 47%
See 1 more Smart Citation
“…Then, it begins to decrease at the age of 20 years in males and females [16]. It has been reported that the serum OC level is 50-150 ng/mL in children, whereas it is 12-20 ng/mL in healthy adults [17]. In our study, the OC level was 87.7±32.7…”
Section: Mortality Rate Of Fop Patientssupporting
confidence: 47%
“…ng/mL in survivors of FOP patients when diagnosed ≤18 years, which was within the reference range of serum OC level in children according to the previous studies [16,17]. However, serum OC level in non-survivors of FOP patients ≤18 years at diagnosis (48.7±15.5 ng/mL), which was below the reference range in the previous studies, was significantly lower than that in survivors.…”
Section: Mortality Rate Of Fop Patientssupporting
confidence: 43%
“…Specifically, a large 8.7 year longitudinal (primarily retrospective) study in the Korean population reported that total OC was not associated with the development of CV disease, although OC values were inversely correlated with obesity and abnormal plasma glucose and lipids [12]. In addition, such relationship was also not found in 476 metabolically healthy Chinese subjects of both genders [20].…”
Section: Osteocalcin and Cardiovascular Riskmentioning
confidence: 99%
“…[27] There has also been a report that in both healthy men and premenopausal and postmenopausal women, osteocalcin has no independent correlation with the carotid intima-media thickness. [28] Therefore, osteocalcin concentration may have a miniscule or limited impact on the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%